DNA-damaging activity of a cinnamate derivative and further compounds from Cinnamomum Australe (Lauraceae) - Carbonezi, C. A.; Lopes, M. N.; Silva, DHS; Araujo, A. R.; Bolzani, V. D.; Young, MCM; Silva, M. R. da (Soc Brasileira Quimica, 2004)
The bioactive compound traps-3'-methylsulphonylallyl traps-cinnamate (1) along with the inactives iryelliptin (2) and (7R,8S,1'S)-Delta8-3',5'-dimethoxy-1',4'-dihydro-4'-oxo-7.0.2',8.1'-neolignan (3) were isolated from the leaves of Cinnamomum australe. The structures of these compounds were assigned by analysis of 1D and 2D NMR data and comparison with data registered in the literature for these compounds. The DNA-damaging activity of 1 is being described for the first time.
Keywords: Cinnamomum australe; Lauraceae; DNA-damaging activity